Hypertension in pregnancy: controversial issues of national and international guidelines - V. S. Chulkov; A. I. Martynov; V. A. Kokorin (Российский кардиологический журнал)
Hypertensive disorders of pregnancy, including pre-existing and gestational hypertension, preeclampsia and eclampsia, complicate up to 10% of pregnancies and represent a significant cause of maternal and perinatal morbidity and mortality. Despite some differences in guidelines, there is consensus that severe hypertension and mild hypertension with organ dysfunction should be managed. However, achieving target values below 160/110 mm Hg remain controversial. The review presents current data on definition, classification, therapy goals and principles used in hypertensive disorders during pregnancy and in the postpartum period in accordance with national and international guidelines.